VerSus project: Lessons from vernacular heritage for sustainable architecture - Guillaud, Hubert (2015)
The project’s main aim is to gain knowledge from the fundamental lessons and principles of the vernacular architecture, and to explore new ways to apply those principles into modern sustainable architecture. The research was developed on the framework of VerSus: Lessons from Vernacular Heritage for Sustainable Architecture, a European research project developed by ESG/Escola Superior Gallaecia, Portugal, as Project leader; with the partnership of UPV/Universitat Politènica de València, Spain; UNICA/Università degli Studi di Cagliari, Italy; UNIFI/Università degli Studi di Firenze, Italy; and CRAterre-ENSAG/ International Centre for Earthen Architecture at Grenoble National Higher Educational School of Architecture, France. The project also received the support of the Chair UNESCOEarthen Architecture, Building Cultures & Sustainable Development, ICOMOS-ISCEAH and ICOMOS-CIAV.